1998
DOI: 10.1128/iai.66.4.1726-1734.1998
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Susceptibility to Shiga Toxin-Producing Escherichia coli O157:H7 by Protein Calorie Malnutrition in Mice

Abstract: Infection with Shiga toxin (Stx)-producing enterohemorrhagicEscherichia coli is increasing among children. In this study, 5-week-old C57BL/6 mice with protein calorie malnutrition (PCM) that had been fed a 5% protein diet for 2 weeks since ablactation were inoculated intragastrically with 2 × 106 CFU of Stx-producing E. coli O157:H7. More than 75% of infected mice with PCM died by 10 days postinfection. Infected mice with PCM developed neurologic symptoms 5 days after infection, while well-nourished control mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 46 publications
(39 reference statements)
0
25
0
1
Order By: Relevance
“…Immaturity includes a non-specific defence system along with a mucosal adaptive immune system not fully developed, so that the physical barrier of intestinal epithelia has an increased permeability in comparison with adult mice. Similarly, Kurioka et al suggested that, in malnourished adult mice, permeability of epithelia is increased, and therefore it is possible that not only Stx but also lipopolysaccharide (LPS) O157 is absorbed through the intestinal epithelia in both models [18]. It has been largely reported that LPS increases the in vitro and in vivo cytotoxic effects of Stx.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immaturity includes a non-specific defence system along with a mucosal adaptive immune system not fully developed, so that the physical barrier of intestinal epithelia has an increased permeability in comparison with adult mice. Similarly, Kurioka et al suggested that, in malnourished adult mice, permeability of epithelia is increased, and therefore it is possible that not only Stx but also lipopolysaccharide (LPS) O157 is absorbed through the intestinal epithelia in both models [18]. It has been largely reported that LPS increases the in vitro and in vivo cytotoxic effects of Stx.…”
Section: Discussionmentioning
confidence: 99%
“…Renal damage in weaned mice fed with Stx-producing bacteria would indicate that the toxin has reached systemic circulation, and the close association between high urea levels, prompt neutrophilia and death suggests that kidney is On the other hand, in the malnourished model mice died after 6 days of oral E. coli O157:H7 infection with signs of neurological but not renal injury [17,18]. Similarities between both, malnourished and weaned mouse models, such as the incomplete development of intestinal epithelia and mucosal immune response, can account for the Stx passage to circulation, and consequently systemic complications.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic circulation of Shiga toxins induces renal tubular injury in mice, but standard laboratory strains of naive mice are resistant to gastrointestinal colonization by STEC (18,19). Previous approaches to induce susceptibility to STEC colonization include severe protein restriction, high-dose antibiotic treatment, and germ-free conditions (17,(20)(21)(22). Colonization may follow, but these models have proven difficult to reproduce, the commensal microbiome is grossly ablated, and germ-free conditions are not generalizable due to altered host responses to pathogens in the absence of host-microbiota interactions (2).…”
mentioning
confidence: 99%
“…In contrast to rabbits, mice and rats given Stx or STEC do not consistently develop diarrhea, colitis or A/E lesions, however they do demonstrate some renal and neurologic pathology 85,412 . Numerous mouse strains have been tested, including C57BL6, CD-1, C3H/HeN, C3H, HeJ, and BALB/c, and the results are comparable between strains 94,116,119,394,[398][399][400][401][402][403][404][405][406][407][408][409][410][411][412][413]427 . Rat strains used include Sprague-Dawley and Wistar, and again the results are relatively equivalent between strains 394,[414][415][416] .…”
Section: Animal Models Of the Hemolytic Uremic Syndromementioning
confidence: 96%
“…Grossly, Gb3 staining and Stx targeting is seen in all three main murine renal compartments, the cortex medulla and papilla, however the specific cellular localization is disagreed upon 94,116 . One group of reports describe toxin binding to and Gb 3 expression on subsets of proximal, distal, and collecting duct tubular cells within the renal parenchyma 94,116,408,410,414,427,435 . Other publications demonstrate Stx interaction with or Gb 3 expression on glomeruli, the renal vasculature, and other vascular cells [398][399][400] .…”
mentioning
confidence: 99%